The Water Taxi Operators Commitment - Bahyah, Abdul Halim (2014)
The Water Taxi services started in the early 1950s at the Terengganu River operating from the Syahbandar Jetty to the Kg. Seberang Takir Jetty. It takes only 10 minutes to travel across the Terengganu River. The Water Taxi service operates to support the village people or tourists to commute from the village to the Waterfront Heritage City. The Water Taxis are built traditionally by the local Terengganu community. Before the construction of the Sultan Mahmud Bridge, the Water Taxi was an important mode of transportation. According to Cooke et al. (2007), Water Taxi Operators provide sufficient services for the local community and traders to transport goods.